KONSTRUKSI SOSIAL KEAGAMAAN PEKERJA LADY COMPANION: STUDI PADA REMAJA GENERASI Z DI MARINDAL, DELI SERDANG - Nilam Sari; Aulia Kamal (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
The transformation of teenage prostitution through digital platforms has created the Lady Companion (LC) phenomenon involving Generation Z youth in Indonesia. This study aims to analyze the socio-religious construction of LC in Marindal, Deli Serdang, a buffer zone of Medan City, by integrating the dimensions of Islamic religious values within the framework of Berger and Luckmann's (1966) social construction theory. This qualitative research using a case study approach involved eight informants: four adolescent perpetrators of LC aged 16-18, two community members, one community leader, and one religious leader. Data were collected through in-depth interviews and non-participatory observation from July to December 2025, then analyzed using thematic analysis. This study found three things; First, there are four factors driving adolescent involvement in LC; (1) structural factors (weak family supervision); (2) economic factors (survival and consumer pressures); (3) peer influence (in-group recruitment and normalization); (4) and the role of social media (content exposure and transaction facilities). Second, the social construction process takes place through (1) externalization (initial exposure to peers and digital media); (2) objectivation (normalization of LC as a common reality in peer groups); (3) and internalization (acceptance of LC as a self-identity and redefinition of self-esteem, sexuality, and work). Third, Islamic religious values have also experienced a shift from absolute moral norms to secondary ones in the face of economic pragmatism. Theoretically, this study expands the theory of social construction by showing digital media as a dominant agent of externalization in the digital era and integrating the religious dimension in the analysis of social construction. Practically, the findings imply the need for an integrated approach involving strengthening the family economy, digital literacy based on religious values, and revitalization of religious institutions with a contextual approach.